2018
DOI: 10.5935/0004-2749.20180078
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric fixation patterns, clinical findings, and reading speed in patients with bilateral toxoplasmic macular retinochoroiditis

Abstract: Myopia is more prevalent in patients with toxoplasmic macular retinochoroiditis. Reading speed is not dependent on preferred retinal locus position, stability, or visual acuity. Nevertheless, documentation of fixation provides new data on the impact of visual impairment in these patients and may be useful for rehabilitation efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the literature, single/multiple PRL development in AMD has been reported at different rates (77%-100%), 1 , 6 , 7 , 8 and most are located extrafoveally. Greenstein et al 6 reported that all patients in their study developed a PRL, of which 73.3% were extrafoveal and 26.6% were foveal in location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, single/multiple PRL development in AMD has been reported at different rates (77%-100%), 1 , 6 , 7 , 8 and most are located extrafoveally. Greenstein et al 6 reported that all patients in their study developed a PRL, of which 73.3% were extrafoveal and 26.6% were foveal in location.…”
Section: Discussionmentioning
confidence: 99%
“… 31 While there are some studies suggesting that location may be relevant in terms of reading, 7 , 32 others showed no relationship between PRL location and reading speed. 2 , 33 , 34 Evidence indicates that PRLs are usually located to the left of the scotoma. 1 , 2 , 7 , 9 , 35 However, PRLs can develop in any retinal quadrant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This locus is known as preferred retinal locus, showing an association with the abnormal head position adopted by some patients during activities of daily living. 40 Another explanation, according to Mets et al, 39 is that, in some cases of extensive central lesions, an essential part of the macula might have been spared. We concluded that even in the presence of extensive macular lesions in a young child, it is not possible to predict the final visual function.…”
Section: Discussionmentioning
confidence: 99%
“…Just as in this study, the literature describes strabismus as the second most frequent ocular manifestation after retinochoroiditis and, quite often, this is the sign that alerts to an ocular lesion in a child without previous diagnosis of toxoplasmosis. 30,36,41 Antunes-Foschini et al 40 underscore the importance of rehabilitation and of rigorous follow-up since childhood, and the importance of stimulation of both eyes, as one cannot know which eye will be the dominant one when the visual system is fully developed.…”
Section: Discussionmentioning
confidence: 99%